(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1943)
The great storms of 1940 blew the sand from the wall-tops of another complex of structures at Freswick. Excavation exposed a single complex of buildings, obviously representing more than one architectural period. The earliest phase of the complex is represented by a "long house" the centre of which was occupied by a long fire represented by a bed of peat ash. The house was subsequently added to with other rooms. Three phases of construction were identified. Bone and stone whorls, loomweights, a net sinker, a bone pin, part of a rotary quern, a gaming piece and some pottery were recovered.